Assessing the protistan functional diversity in soil and roots of common crops in Sapa district, Lao Cai province, Vietnam - Nguyen, Hung; Herrmann, Laetitia; Dung, Le Viet; Lesueur, Didier (2025)
The traditional method of relying on described phenotypic characteristics of protistan taxa is commonly relied upon for taxonomy-based functional classifications. Here, this method provided a broad overview of the functional diversity of protists, specifically suggesting that consumers dominated the protistan communities. However, further analysis of just two taxa (i.e., the only two that could be examined) found the commonly utilized classifications to not be encompassing enough (Adl et al. 2019). Both taxa had additional potential trophic functions proposed, with Ciliophora potentially (also) parasitic, and significant evidence that Euglyphida is phototrophic. The latter classification significantly alters the initial functional diversity assessment, where it originally seemed as though there were no significant phototrophic taxa, despite most studies having identified at least a few representatives of each of the three trophic functional groups in their experiments. Unfortunately, limitations in available genomic data do not allow more robust genotypic analyses of other protistan taxa.